2020
DOI: 10.1073/pnas.2004262117
|View full text |Cite
|
Sign up to set email alerts
|

EYES ABSENT and TIMELESS integrate photoperiodic and temperature cues to regulate seasonal physiology in Drosophila

Abstract: Organisms possess photoperiodic timing mechanisms to detect variations in day length and temperature as the seasons progress. The nature of the molecular mechanisms interpreting and signaling these environmental changes to elicit downstream neuroendocrine and physiological responses are just starting to emerge. Here, we demonstrate that, inDrosophila melanogaster, EYES ABSENT (EYA) acts as a seasonal sensor by interpreting photoperiodic and temperature changes to trigger appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 71 publications
2
38
0
Order By: Relevance
“…Knockdown of eya in IPCs causes an increase in the size of the ovary, implying that Eya negatively regulates oogenesis through IPCs. Interestingly, the expression of eya has a circadian rhythm (Abrieux et al, 2020). More precisely, the peak of Eya protein levels is delayed in the short-day condition in comparison to the long-day condition.…”
Section: Mechanisms Of Dormancy Control By Circadian Clocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockdown of eya in IPCs causes an increase in the size of the ovary, implying that Eya negatively regulates oogenesis through IPCs. Interestingly, the expression of eya has a circadian rhythm (Abrieux et al, 2020). More precisely, the peak of Eya protein levels is delayed in the short-day condition in comparison to the long-day condition.…”
Section: Mechanisms Of Dormancy Control By Circadian Clocksmentioning
confidence: 99%
“…This fact implies that reproductive dormancy in D. melanogaster has both quiescence and diapause properties. Therefore, most papers published in recent years simply use "dormancy" to describe the short-day and low temperatureinduced changes in D. melanogaster adults (Kubrak et al, 2016;Liu et al, 2016;Andreatta et al, 2018;Lirakis et al, 2018;Ojima et al, 2018;Nagy et al, 2019;Abrieux et al, 2020). In this paper, as is customary, we will refer to the D. melanogaster phenotypes in terms of dormancy.…”
Section: An Overview Of Drosophila Melanogaster Dormancymentioning
confidence: 99%
See 1 more Smart Citation
“…Even lower temperatures (<14°C) in combination with short photoperiods induce diapause or reproductive dormancy in D. melanogaster ( Saunders and Gilbert, 1990 ). It has recently been shown that accumulation of the cotranscription factor EYES ABSENT (EYA) is required for an efficient transition to female diapause ( Abrieux et al, 2020 ). Interestingly, TIM-SC is the major Tim isoform under 10°C, and presumably binds to, and stabilizes EYA under these conditions, thereby promoting diapause entry.…”
Section: Direct Effects Of Temperature On Per and mentioning
confidence: 99%
“…The tyrosine phosphatase-dead form of EYA3 was able to potentiate TEF/SIX1-mediated TSHβ transcription to levels comparable to the wild-type protein [ 58 ], suggesting that the tyrosine phosphatase activity is dispensable for EYA3's role in photoperiodism. Collectively, the currently available evidence supports a role for EYA3's transactivation activity in measuring night length and tuning the circadian clock with seasonal changes [ 60 ].…”
Section: Eya In Photoperiodismmentioning
confidence: 99%